Constipation in babies and children: Diagnosis and treatment [Bebek ve çocuklarda kabizlik] - (:unkn) unknown (My University, 2006)
Constipation in children continues to be a common and frustrating problem to treat. It has been estimated that up to 3% of visits to pediatricians, and 25% of visits to pediatric gastroenterologists, are motivated by defecation problems. Although no uniform definition exists for constipation, it may be defined as 'a delay or difficulty in defecation, present for two or more weeks and sufficient to cause significant distress to the patients'. Difficulties with defecation may result from dysfunction in any portion of the normal mechanism of defecation. Such dysfunction may result from aberrations in anatomy or physiology. A thorough history and physical examination will uncover the majority of predisposing problems that may contribute to constipation. Most children are adequately treated by appropriate behavioral and life style changes and pharmacologie interventions. Failure of treatment despite good compliance requires reconsideration of the differential diagnosis, further evaluation, and referral to the pediatric gastroenterologist.